Knowledge and Practices of Wound Care Among Animal Bite Cases Attended at Institute of Public Health - Ara, Rowshan; Uddin, Md Nasir; Wahab, Md Abdul; Ferdousi, Shahneela; Khondker, Lubna; Khan, Md Shirajul Islam (Medicine Today, 2013)
Animal bite is common in Bangladesh. A cross sectional type of descriptive study was carried out at the Institute of Public Health (IPH), Dhaka to find out the knowledge and practices related to wound care among animal bite cases during the month of February, 1998. A total of 200 patients were interviewed, 55% of them came from urban area. Maximum (65.5%) patients were teenagers and adult (above 13 yrs.) with mean age 22.15 yrs. Male and female ratio was 80.5:19.5. Majority of cases were poor (76.5%) and only 12% attained educational level of SSC pass or above. In 92.5% cases dog was the biting animal, 60% of which were stray. Only 91(45.5%) patients took immediate measures for wound care. Of them only 11 patients knew and washed the wound by soap and water and 3 patients did it after getting advice from physicians. 134 (67%) patients consulted with physicians one hour to several days after, whereas 33% within one hour. Among the attending physicians 31.5% were MBBS doctors but 57.5% were Kabiraz, Fakir, Moullana and others. In 50 present animal bite cases, Fold remedies or herbal medicine were advised in comparison to 42% for vaccination. But only 3 (1.5%) patients got the message of wound care by washing with soap and water. Emphasis on planning on educational programme on "What people should do after an animal bite" has been recommended. DOI: http://dx.doi.org/10.3329/medtoday.v24i1.14111 Medicine TODAY Vol.24(1) 2012 pp.27-30